UPAYA PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIKA SISWA KELAS VII-B SMP MUHAMMADIYAH 9 YOGYAKARTA MELALUI PENERAPAN PENDEKATAN PEMBELAJARAN PROBLEM POSING - Noviyana, Hesti (LPPM STKIP PGRI Bandar Lampung, 2014)
This study aims to improve the communication skills of mathematical class VII-B SMP Muhammadiyah Yogyakarta through 9 describe the implementation of problem-posingdan learning mathematics through problem posing approach to class VII-B Junior High School 9 of Muhammadiyah Yogyakarta.This research is Classroom Action Research (CAR). The subjects were students of class VII-B grade students of Junior High School 9 of Muhammadiyah Yogyakarta, with as many as 20 students. The experiment was conducted in two cycles. Data were obtained from the observation of the implementation of learning, observation learning approach, test questions, field notes, interviews with students and teachers, as well as documentation.The results showed that learning mathematics through problem posing approach can improve students' communication skills and mathematical achievement KKM class VII-B Junior High School 9 of Muhammadiyah Yogyakarta. The results where the average score communication skills class VII-B that is equal to 76.00 or by classical completeness percentage of 85.71%. This means that the action in the second cycle was up to standard classical completeness. In the second cycle also shows that the achievement of KKM are the criteria quite well with an average of 77.25. It is also supported by the results of interviews conducted to some students and teachers in class VII-B Junior High School 9 of Muhammadiyah Yogyakarta shows that learning mathematics through problem posing approach favored by students and can enhance students' mathematical communication skills.